Effect of Astragalus polysaccharide supplementation on growth performance and plasma parameters of weaned piglets under commercial condition (International Journal of Health, Animal Science and Food Safety, 2018)
The aim of this study was to evaluate the effect of Astragalus polysaccharide (APS) supplementation on the growth performance, plasma biochemical parameters, and plasma immune and antioxidant indexes of weaned piglets in a commercial swine farm. A total of 120 piglets weaned at 22 days and allocated to 2 groups, and fed a basal diet either without (CTR) or with 200 mg/kg of APS in a local commercial farm for a 42-d experiment. At end of the trial, one piglet from each pen was selected for blood sampling. The results showed that dietary APS decreased the feed conversion ratio (FCR) compared to the CTR group from day 14 to day 28 and day 0 to day 42 (P = 0.08 and 0.02, respectively). In addition, supplementation of APS had the tendency to increase the plasma superoxide dismutase activity and IgG content of piglets compared to the CTR group on day 42 (P = 0.06 and 0.09, respectively). Results in this study suggested that dietary APS might have a beneficial effect on growth performance and health status of weaned piglets under the commercial condition.
Keywords: Astragalus polysaccharide; commercial farm; growth performance; plasma parameters; weaned piglets